Aerogel preparation from short cellulose nanofiber of the Eucalyptus species. (September 2017) - Zanini, Márcia; Lavoratti, Alessandra; Zimmermann, Matheus VG; Galiotto, Deise; Matana, Fernando; Baldasso, Camila; Zattera, Ademir J
Wood is the main industrial source for obtaining cellulose. It is a natural composite, constituted by cellulose, polyoses, lignin, small amounts of extracts and mineral salts, wherein cellulose is the most abundant component. Many studies are being developed for obtaining materials based on natural fibers, which combine interesting properties such as renewability, biodegradability, low density and low cost. Aerogels are solid, lightweight materials with high porosity and high internal surface area. These features combined in one single material make the aerogels a differentiated product with potential for use as an adsorbent. In this context, aerogels made of cellulose nanofibers obtained from short-fiber cellulose of Eucalyptus sp. were made. The cellulose suspension was first disintegrated by a mechanical grinder, and the aerogels were undergone to freeze-drying. The characterization of the samples was performed by apparent density, porosity, scanning electron microscopy, Fourier transform infrared spectroscopy and thermogravimetric analyses. According to the micrographs obtained by scanning electron microscopy and field emission gun scanning electron microscopy, it was observed the formation of pores formed by the interconnection of cellulose fibers. The apparent density of the starting cellulose fibers (pressed plates) was 0.6998 g.cm −3 and the aerogel density decreased to 0.0240 g.cm −3 . The values for aerogel porosity were about 97%, which benefits the passage of liquids and gases from the external environment to the internal structure of the material. Fourier transform infrared spectroscopy and thermogravimetric analyses showed no change in the chemical composition or in the thermal stability of the obtained aerogels in comparison to their starting materials.